(untitled) (Research, Society and Development, 2022)
The socio-economic (trans)formations experienced by contemporary societies target inclusive and egalitarian actions that improve life quality. From this phenomenon, the concept of Solidarity Economic Enterprise (EES) is based on the ideals of solidarity, cooperation, and self-management. In this context, the objective of this paper is to present a proposal for a scope review protocol for the EES’s operation, specifically concerning their self-management practices in Brazil. With this protocol, we explore the possible methodological steps for this study. We expect that this scoping review maps the scientific evidence related to SEB’s operation for the self-management practices in the country.